A Mendelian randomization study on the causal effects of cigarette smoking on liver fibrosis and cirrhosis - Guo, Liwei; An, Yong; Huang, Xu; Liu, Wenhua; Chen, Fangfang; Fan, Yuchen; Gao, Shuai; Han, Liyan; Wang, Kai (Frontiers in Medicine, 2024)
Background: Liver fibrosis significantly impacts public health globally. Untreated liver fibrosis eventually results in cirrhosis. Cigarette smoking is the main etiologic factor for various diseases. Even so, the causal effects of cigarette smoking on liver fibrosis and cirrhosis have yet to be fully elucidated.In this study, Mendelian randomization (MR) analysis was performed to assess the association between cigarette smoking, liver fibrosis, and cirrhosis.Single-nucleotide polymorphisms (SNPs) were selected as instrumental variables from a genome-wide association study (GWAS) of European ancestry. Patients were divided into six exposure categories which included "ever smoked", "pack years of smoking", "age of smoking initiation", "smoking status: never", "smoking status: current" and "smoking status: previous". The outcomes of this study included liver fibrosis and cirrhosis. MR-Egger, weighted median, inverse variance weighted, simple mode, and weighted mode were selected as the analysis methods. Cochran's Q and the MR-PRESSO tests were conducted to measure heterogeneity. The MR-Egger method was performed to evaluate horizontal pleiotropy, while the "leave-one-out" analysis was performed for sensitivity analyses.The results of this study showed that having a smoking history increases the risk of liver fibrosis and cirrhosis ("ever smoked": odds ratio [OR] = 5.704, 95% CI: 1.166-27.910, p = 0.032; "smoking status: previous": OR = 99.783, 95%CI: 2.969-3.353e+03, p = 0.010). A negative correlation was observed between patients who never smoked and liver fibrosis and cirrhosis ("smoking status: never": OR = 0.171, 95% CI: 0.041-0.719, p = 0.016). Even so, there were no significant associations between "smoking status: current", "pack years of smoking" and "age of smoking initiation" and liver fibrosis and cirrhosis. Cigarette smoking did not have a significant horizontal pleiotropic effect on liver fibrosis and cirrhosis. "Leave-one-out" sensitivity analysis indicated that the results were stable.The study confirmed the causal effects of cigarette smoking on liver fibrosis and cirrhosis.